FORMULASI DAN UJI KELAYAKAN SEDIAAN KRIM ANTI INFLAMASI GETAH TANAMAN PATAH TULANG (Euphorbia tirucalli L) (PHARMACON, 2013)
ABSTRACTHas been formulated the latex of pencil tree plant (Euphorbia tirucalli L) to be a cream.Pencil tree plant latex cream formulated with various concentrations of the active substancesi.e 5%, 10%, and 15%. The formulation of pencil tree plant latex cream produced the cramwith good parameter values.Key words : Cream, Pencil Tree Plant (Euphorbia tirucalli L)